A comprehensive investigation of energy management practices within energy intensive industries in Bangladesh. (1st October 2021) - Hasan, A S M Monjurul; Tuhin, Rashedul Amin; Ullah, Mahfuz; Sakib, Taiyeb Hasan; Thollander, Patrik; Trianni, Andrea
Abstract: Industrial energy efficiency is acknowledged as a cost-effective mean contributing to sustainable development and industrial competitiveness. Implementing energy management practices becomes even more imperative for developing countries, considering their energy usage trends and economic development forecasts. Based on the circumstances, an empirical investigation is conducted on energy efficiency and management practices, as well as barriers and drivers to energy efficiency in the energy-intensive industries of Bangladesh. The study finds that majority of the companies barely implement the energy management practices. Energy audits represent the mostly implemented energy management practice at the industries, though a comprehensive approach on a detailed level is still lacking. In addition, this study finds that the number of dedicated and specialised energy professionals employed in the industries is yet negligible. The cumulated results show that energy efficiency is mostly disrupted due to inadequate support from preeminent administration and bureaucratic intricacy. Energy blueprint cost-saving due to less use of energy and rules and regulations were distinctively signified as most imperative drivers for energy efficiency. On the other hand, lack of information is found to be the most significant barrier to consult energy service companies. Analysis of the country's energy usage and supply-demand relationship points towards insufficient energy efficiency measures and energy management practices in the country. The study also finds that energy efficiency could be improved by 8%–10% through the practice of energy management. Our findings, besides pointing out specific issues to be tackled in the specific context of investigation, pave the way for further research over industrial energy efficiency in developing countries. Highlights : Industrial energy efficiency in developing countries has received little attention. Barriers, drivers and energy management practices have been discussed in Bangladesh. 8–10% improvement by implementing energy management in Bangladesh is recognised. Bangladeshi energy intensive industries are lacking specialised energy professionals. Energy blueprint can boost energy efficiency in Bangladeshi energy intensive firms.